Inclusive labor market development through green economy and social responsibility - Tsymbaliuk, Iryna O. (Innovatio Press, Lublin, 2024)
The article explores global challenges for the labor market in the context of the transition to a green economy. The primary focus is on structural changes in traditional sectors of the economy and the need for workforce adaptation to new requirements associated with the implementation of environmental technologies. Provides an overview of international data, particularly OECD reports, which highlight the risks of job losses in traditional industries and the uneven creation of new jobs in the green economy. Regional disparities are also examined and illustrated with charts and tables that show employment levels in green sectors and the differences between regions and countries. The article also analyzes workforce risks, particularly the need for retraining workers in sectors most affected by these changes. Special attention is given to gender inequality in the labor market. Data on the gender employment gap in green sectors, where women are underrepresented, is presented, along with wage disparities between men and women in these industries. Significant attention is also devoted to the role of corporate social responsibility (CSR) in supporting an inclusive labor market. The article analyzes how CSR contributes to workforce retraining, ensuring equal access to new jobs, and fostering local economic development. Pathways for reducing economic inequality between regions, increasing inclusion, and promoting gender equality are proposed through the implementation of government support programs and the active involvement of businesses in socially responsible projects.
Keywords: inclusive approaches; labor market; green economy; social responsibility; gender inequality; economic inequality; employment